Challenges in the Implementation of STEM in Islamabad - Ayesha Maqsood; Rashda Parveen; Nadeem, Muniza (JSE, 2025)
It is critical to prepare students to cater for the problems of twenty first century challenges through integration of Science, Technology, Engineering, and Mathematics (STEM) education. While policy initiatives in Pakistan have increasingly emphasized STEM, many institutions are trying hard to implement STEM effectively but the effective implementation in Islamabad schools remains uneven. The main purpose of this study was to explore the challenges of implementing STEM education in the locale of Islamabad. It was a qualitative study in which phenomenology design was used to learn about the lived experiences of participants. Data was collected through semi structured interviews. The participants of the study were science teachers with experience of five years of teaching in Islamabad Capital territory. Ten science teachers from Islamabad Capital Territory institutions and ten from private institutions were purposefully selected for interviews. Data was analyzed through thematic analysis. The themes that evolved through interviews were necessary infrastructure, teacher training, curriculum and assessment design, and policy-practice gaps. Key challenges include moderate teacher content and pedagogical knowledge, limited resources (labs, ICT), rigid, exam oriented curricula, and insufficient policy support and monitoring. Keeping in view the key findings, it was recommended for effective STEM education implementation in Islamabad schools can be done through teachers training in STEM education, improvement in infrastructure, curriculum reforms, public involvement and policy framework development and implementation.